The chromosome-level genome of dragon fruit reveals whole-genome duplication and chromosomal co-localization of betacyanin biosynthetic genes. (10th March 2021) - Zheng, Jinfang; Meinhardt, Lyndel W; Goenaga, Ricardo; Zhang, Dapeng; Yin, Yanbin
Abstract: Dragon fruits are tropical fruits economically important for agricultural industries. As members of the family of Cactaceae, they have evolved to adapt to the arid environment. Here we report the draft genome of Hylocereus undatus, commercially known as the white-fleshed dragon fruit. The chromosomal level genome assembly contains 11 longest scaffolds corresponding to the 11 chromosomes of H. undatus . Genome annotation of H. undatus found ~29, 000 protein-coding genes, similar to Carnegiea gigantea (saguaro). Whole-genome duplication (WGD) analysis revealed a WGD event in the last common ancestor of Cactaceae followed by extensive genome rearrangements. The divergence time between H. undatus and C. gigantea was estimated to be 9.18 MYA. Functional enrichment analysis of orthologous gene clusters (OGCs) in six Cactaceae plants found significantly enriched OGCs in drought resistance. Fruit flavor-related functions were overrepresented in OGCs that are significantly expanded in H. undatus . The H. undatus draft genome also enabled the discovery of carbohydrate and plant cell wall-related functional enrichment in dragon fruits treated with trypsin for a longer storage time. Lastly, genes of the betacyanin (a red-violet pigment and antioxidant with a very high concentration in dragon fruits) biosynthetic pathway were found to be co-localized on a 12 Mb region of one chromosome. The consequence may be a higher efficiency of betacyanin biosynthesis, which will need experimental validation in the future. The H. undatus draft genome will be a great resource to study various cactus plants.